Analysis of communities and groups in social networks as a significant factor of influence on cryptocurrency rates - Olena Gavrilenko; Mykhailo Myagkyi (Сучасний стан наукових досліджень та технологій в промисловості)
Currently, most existing cryptocurrency exchanges do not have tools in their arsenal that would allow them to verify and investigate information disseminated on social media regarding a particular cryptocurrency. This allows to conduct research with the subsequent development of an appropriate tool that, if used correctly, will provide users with recommendations on how to proceed with the cryptocurrency under investigation. Based on this advice, interested parties will be able to adjust their decisions regarding further financial steps. As part of this task, it is important to choose a social network that would best meet the requirements, as this is what determines the impact of celebrity publications on the formation of prices for a particular cryptocurrency at a certain point in time. The importance and existence of this influence has been previously proven by statistical methods. The purpose of the study is to identify and analyse the key aspects when choosing social networks for further monitoring of social groups in order to analyse the impact of posts on the course of the chosen cryptocurrency. The object of the study is social networks. A set of selection criteria, coefficients of their importance, and statistical data on the selected social networks were used as input data, on the basis of which the values of the alternatives (social networks) will be obtained. The objective of the study is to evaluate and rank social networks in order to choose the one that will best meet the specifics of analysing the impact of social media posts on the cryptocurrency rate. Research methods. The ranking of social networks was carried out by the value of the value function of alternatives, calculated using the linear convolution method. Results. As a result of the research, an algorithm has been developed that allows analysing the selected social networks for their compliance with the formulated criteria. The results of the experiment with the selected social networks were presented. As a result, a ranked list of them is obtained. Based on the results obtained, the authors will develop an information technology for determining the impact of posts of famous people in social networks on cryptocurrency rates.